THE PRAGMATICS OF POLITENESS: ANALYZING ‘FACE’ AND INDIRECTNESS IN MODERN ENGLISH DISCOURSE - Umaraliyev Mukhriddin (Ta’lim innovatsiyasi va integratsiyasi, 2026)
This article analyzes the sociolinguistic constructs of politeness within the English language. By applying the "Politeness Theory" of Brown and Levinson, the paper explores how speakers use linguistic strategies to mitigate "Face-Threatening Acts" (FTAs). The study examines the distinction between positive and negative politeness and its implications for cross-cultural communication in an English- speaking context.